Implementation of Assignment Methods Through Social Media: A Case Study of Pancasila Courses - Mina Umrah Pelas; Suharno Suharno (Journal of Islamic Education and Ethics, 2023)
The COVID-19 pandemic is one of the causes of the implementation of online learning, which requires students to be more active in cyberspace by relying on digital platforms with features that support the smooth online learning process. In addition to the implementation of online learning, students also collect assignments and submit them online and upload them on each student's social media. This study aims to test the effectiveness of the learning method by giving assignments through social media. This research method is qualitative with a case study approach. The informants in this study were students in the Pancasila Course. The results showed that three social media were agreed to be a place to upload assignments given by lecturers such as social media Instagram, Facebook, and YouTube. Giving assignments that will be uploaded on social media provides its own creativity for students. With the independent task of finding information in the surrounding environment, students are active and enthusiastic in learning directly from the natural surroundings and more creative in using social media for learning purposes.